P187 Individual differences in parietal theta frequency drive spatial working memory capacity. Issue 3 (March 2017) - Romei, V.; Cooper, N.; Sauseng, P.; Wolinski, N.
Abstract : The speed of fronto-parietal theta oscillatory activity is thought to play a key role in determining working memory (WM) capacity. Individual differences in the length of a theta cycle (ranging between 4 Hz and 7 Hz) might act as an envelope for nested gamma cycles (>30 Hz). This would provide the fundamental neurophysiological mechanism for working memory storage accounting for individual differences in the maximum number of items (number of gamma cycles) retained in the working memory buffer (one theta cycle). Accordingly, it would be expected that slower theta frequencies bind a higher number of gamma cycles per memory buffer resulting in increased memory capacity. Conversely, faster theta frequencies would bind a comparatively smaller number of nested gamma cycles, corresponding to decreased memory capacity. We directly tested this hypothesis by means of right parietal transcranial Alternating Current Stimulation (tACS). Specifically, we tested for the impact of down-regulation (4 Hz tACS) and up-regulation (7 Hz tACS) of theta oscillations in a spatial WM paradigm. To this aim eleven participants underwent 4 Hz, 7 Hz and sham stimulation while performing a variation of the Sternberg task. In line with our hypotheses, results showed that down-regulation of right parietal theta by 4 Hz tACS enhanced WM capacity while up-regulation of right parietal theta frequency by 7 Hz tACS reduced WM capacity compared to sham stimulation. These effects were found only for items presented to the left hemifield, i.e. contralateral to the stimulation site, thus providing causal evidence for frequency and spatially tuned WM capacity organization. In conclusion, we provide the first causal evidence that inducing slower parietal theta frequency activity results in higher working memory capacity, while inducing faster parietal theta frequency activity results in reduced working memory capacity, in line with the theta-gamma phase coupling theory of WM capacity.